The Effectiveness of Using Canva Toward Students Writing Ability of Achievement Student of SMP Negeri 3 Mardingding - Emya Gresta Br Sembiring; Yulia Sari Harahap (PT Inovasi Pratama Internasional, 2023)
Many junior high school students do not understand the importance of writing for student achievement. This study intends to determine whether or not the use of the Canva application is effective as a medium for student achievement in writing. This research uses quantitative methods. The instruments used in this study were interviews and tests. Respondents in this study were students of class VIIIA and class VIIIB of SMP Negeri 3 Mardingding. The results showed that the effectiveness of Canva on students' writing skills was that there were 25 students in class VIIIA and 25 students in class VIIIB, and class VIIIB learned to write using Canva in the computer laboratory. and class VIIIA don't use canva. It turns out that learning to use Canva is more effective than not using Canva. class VIIIB understands and understands Canva better because they directly use it, this can be seen from the test results that students are more creative in writing compared to students who do not write from Canva.